Analisis kebugaran jasmani siswa: Studi komparatif antara ekstrakurikuler bolabasket dan futsal - Suryadi, Didi (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
Physical fitness is one of the most important aspects to improve sports performance. However, currently extracurricular at school is that there is no clear planning, goals and objectives for conducting physical fitness tests. This study aims to compare the level of extracurricular physical fitness of basketball and futsal. This research method uses a quantitative approach through a survey where the researcher gives tests and measurements to basketball and futsal extracurricular students. The sampling technique used purposive sampling so that a sample of 40 students consisted of 20 extracurricular basketball students and 20 futsal students at Madrasah Tsanawiyah Negeri 1 Pontianak. The research instrument is the Indonesian Physical Fitness Test (TKJI) aged 13-15 years. The research was conducted on 19-25 February 2021. Data analysis used descriptive percentage, assisted by using Microsoft Excel software application. The results of the physical fitness test showed an average difference of 2.5, so there was a significant difference between basketball extracurricular students and futsal extracurricular students. This needs to be considered and taken into account by coaches and sports teachers in providing training programs to students. Based on the results of this study, it can be interpreted that basketball extracurricular has a good contribution compared to futsal extracurricular for students' physical fitness.